Biodiversitas dan Potensi Jamur Makroskopis di Cagar Alam Ulolanang Kecubung Batang Jawa Tengah - Ami Nurohmah; Muhammad A’tourrohman; Lianah Lianah (Gunung Djati Conference Series, 2021)
Ulolanang Kecubung Nature Reserve in Batang Regency is a lowland forest type with a relatively high level of plant species biodiversity, so it is possible to find many macrofungi types in it. This study aimed to provide information about the biodiversity of microscopic fungi in CA Ulolanang Kecubung, and its potential future uses. Macroscopic mushroom type data collection was carried out by exploration method, namely exploring the randomly represented area, then continued by recording the number of individuals and sample documentation. Macro fungi were collected in the area of CA Ulolanang Kecubung on pal 22 - 43. Identification of macrofungi was carried out at LIPI Cibinong Bogor using macroscopic characters. Information on its use as food (edible or non-edible) and other potentials is obtained through interviews with key persons and literature studies. A total of 5 types of fungi have been successfully obtained and identified, including (1) Marasmeillus sp., (2) Amauroderma sp., (3) Termitomycetes sp., (4) Ascomycota cookiena, and (5) Pleurotus ostreatus. Each fungus has potential as (1) decomposers, (2) a cancer drug composition, (3) gastrointestinal infection drugs, (4) traditional medicine, (5) Antioxidant and hepatoprotective.